Added Value of Dynamic Contrast-Enhanced Magnetic Resonance Imaging in Predicting Advanced Stage Disease in Patients With Endometrial Carcinoma. Issue 1 (1st January 2009) - Sala, Evis; Crawford, Robin; Senior, Emma; Shaw, Ashley; Simcock, Bryony; Vrotsou, Kalliopi; Palmer, Christopher; Rajan, Pauline; Joubert, Ilse; Lomas, David
Abstract : Aim: To assess the added value of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in predicting advanced stage disease in patients with endometrial carcinoma. Materials and Methods: Fifty patients with endometrial carcinoma underwent preoperative MRI assessment in a single gynecological cancer center during a 2-year period. Magnetic resonance imaging examinations included high-resolution sagittal, axial, and axial-oblique T2-weighted images (T2WI) of the pelvis, and axial T1-weighted images (T1WI) of the pelvis and upper abdomen followed by DCE-MRI using a multiphase 3-dimensional gradient refocused echo T1WI sequence. The T2W images were evaluated initially, and local and overall staging was assigned according to the FIGO classification. An identical scoring system was used to evaluate the combination of DCE-MRI and T2WI. The presence of potential pitfalls in the accurate assessment of depth of myometrial invasion (leiomyoma, adenomyosis, loss of junctional zone definition, polypoid tumor, poor tumor-to-myometrium contrast, and tumor extension to uterine cornu) was also recorded. Surgical histology constituted the standard of reference. Results: The depth of myometrial invasion was correctly determined in 78% (39/50) of the cases on T2WI alone, increasing to 92% (46/50) with the addition of DCE-MRI (95% confidence interval for improvement, 4.4%-23.6%, P = 0.016). The addition of DCE-MRI led to the correct detection of deep myometrial invasion in all cases. Tumor extension to uterine cornu was the only variable significantly associated ( P = 0.014) with incorrect estimation of depth of myometrial invasion. Conclusions: The addition of multiphase 3-dimensional DCE-MRI to T2WI can effectively assess the depth of myometrial invasion in endometrial carcinoma and may be a useful tool to guide the surgical approach.